A journey of self-discovery through the unconscious: A study of Kazuo Ishiguro’s The Remains of The Day (1989) - Mohammad, Einas Abashar Ahmed (Research Journal in Advanced Humanities, 2024)
Ishiguro is a postmodernist writer who was concerned with considering the past from a late twentieth century postmodernist perspective. His novels are narrative that deal with human relationships and center on the working of the consciousness and the unconsciousness of the mind. The present study investigates the impact of the two World Wars on the mind and soul of the modern man as represented in Ishiguro’s The Remains of The Day. It traces the role of memories in creating a meaningful present. Stevens -the protagonist- seeks to come to terms with his present through unconsciously recalling past memories. The novel depicts the role of memories in constructing meaningful present and discovering oneself in some way from a psychoanalytic postmodernist perspective. As a postwar British character, Stevens suppresses his emotions at the personal as well as the professional levels to construct a new identity. He is suffering from an identity crisis and striving to create a meaningful present for himself through reminiscence. As a postmodernist individual, Stevens is leading a life riddled with inconsistencies and contradictions. He does not feel at home with the surrounding present world as he is busy trying to achieve some perfection through recollecting his past memories. The study aims to answer the following questions: How does Stevens struggle to discover his self through recalling past memories? What strategies does he adopt to adapt to the new world to harmonize both the past and the present? What kind of life is the protagonist living and how is he compelled to tell lies to maintain a new self from a postmodern perspective?